Optimalisasi Potensi Desa Untuk Meningkatkan Perekonomian Desa Watugajah - Ludvianto, Meganusa (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
UAJY Community Service based on Society 5.0 is a sustainable step to continue to provide innovation and community service even during the COVID-19 pandemic. Group 78 of the 79 Community Service Program conducted community service in Watugajah Village, Gedangsari District, Gunung Kidul Regency. The purpose of this service is to improve the economy of Watugajah Village by optimizing the village's potential. This service is expected to be able to provide education and information to the community because there are many potentials in Watugajah Village that are not maximized in its operations. Therefore, this optimization aims to increase the added value of the tourism, handicraft, and food processing sectors, especially night mango. The methods used to realize the work program are the method of determining the topic by searching for data related to Watugajah Village information, the method of searching for literature by looking for theories and sources from experts to strengthen related data, methods of making reports, e-books, and videos that will be provided to the community to provide knowledge in improving the economy of the Watugajah Village community, and methods of discussion and guidance carried out together with supervisors. The result is that the community can practice optimizing tourism, crafts, and food processing. Making fertilizers also affect increasing community independence in fertilizer production. The conclusion is that the increase in the potential of the village can encourage the economy of the people of Watugajah Village.